Isolation and Identification of Crude Triacontanol from Rice Bran Wax - Avinash Ade2, Sandhya Jaybhay1*, Pankaj Chate1 and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; background: white; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> In present investigation crude triacontanol was isolated and identified from rice bran wax. Triacontanol was isolated by saponification and extraction method. The obtained mixture is crude Triacontanol. It was analyzed by Gas Chromatography (GC) and melting point method. Purity of triacontanol was 13.33%. Â 1Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad (M.S.), India; 2Department of Botany, University of Pune, Pune (M.S.), India * Corresponding Author, Email: jsandhya86@yahoo.in Please Cite This Article As: Sandhya Jaybhay, Pankaj Chate and Avinash Ade. 2010. Isolation and Identification of Crude Triacontanol from Rice Bran Wax. J. Exp. Sci. 1(2): 26.